The exo-planetary system of 55 cancri and the titius-bode law - Patricia Lara (Revista Mexicana de Astronomía y Astrofísica, 2008)
The recent discovery of a fifth planet bound to 55 Cancri (Fischer et. al2007) motivated us to investigate if this exo-planetary system fits some form of theTitius-Bode (TB) law. We found that a simple exponential TB relation reproducesvery well the five observed major semi-axis, provided we assign the orbital n = 6to the largest a. This way of counting leaves empty the position n = 5, a situationcuriously reminiscent of TB law in our planetary system, before the discovery ofCeres. The application of an exponential TB relation to 55 Cancri allows us topredict the existence of a planet at a ~ 2.0 AU with a period of P ~ 1130 dayslocated within the large gap between a = 0:781 AU (P = 260 days) and a = 5:77 AU(P = 5218 days). With less certainty, we also predict a seventh planet at a ~ 15 AU,with P ~ 62 years.